2006
DOI: 10.1177/1557234x0600200102
|View full text |Cite
|
Sign up to set email alerts
|

Situation Awareness Catches On: What? So What? Now What?

Abstract: Human factors/ergonomics professionals regularly study the situation awareness (SA) problems of pilots, air traffic controllers, automobile drivers, power plant workers, ambulance dispatchers, urban search and rescue professionals, and unmanned vehicle operators, to mention a few. The challenge has been to define SA operationally and devise measurement strategies that focus on attention and recall on the one hand and relevant actions on the other. Although there have been many successes, challenges remain. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 60 publications
1
28
0
Order By: Relevance
“…For example, an eye tracker system has been incorporated into the virtual mask and can be used to record the subjects' visual fixation points within the field of view. This information can be used to assess situational awareness [84,85], an important element of workplace safety in and around vehicles. It can also be used to determine experimental lines of sight that can supplement envelopes of sight defined using models [86].…”
Section: Laboratory Studiesmentioning
confidence: 99%
“…For example, an eye tracker system has been incorporated into the virtual mask and can be used to record the subjects' visual fixation points within the field of view. This information can be used to assess situational awareness [84,85], an important element of workplace safety in and around vehicles. It can also be used to determine experimental lines of sight that can supplement envelopes of sight defined using models [86].…”
Section: Laboratory Studiesmentioning
confidence: 99%
“…Meanwhile, SA has been applied to many areas in which operators act in complex dynamically changing environments and where automation of task processes becomes more and more prevalent (Durso & Sethumadhavan, 2008;Wickens, 2008). While the intuitive notion of "knowing what is going on around you" (Endsley, 2000b, p. 5) as a prerequisite for successful performance is most widely accepted by human factors researchers; the status of SA as a concept, its definition and measurement is still subject to an ongoing debate (e.g., Dekker & Hollnagel, 2004;Durso, Rawson, & Girotto, 2007;Flach, 1995;Gelau & Krems, 2009;Rousseau, Tremblay, & Breton, 2004;Sarter & Woods, 1991;Tenney & Pew, 2006).…”
Section: What Is Situation Awareness?mentioning
confidence: 99%
“…The current lack of perfect automation means that it is necessary for a human user to maintain optimal SA (high vigilance) to be able to intervene in a timely manner, particularly in tasks of high consequence. However, vigilance studies have shown that maintaining this level of SA over time is extremely difficult [6]. Maintaining optimal SA requires the ability to measure SA levels frequently, and perhaps continuously, in order to determine when SA levels become suboptimal.…”
Section: Situation Awareness and Its Importance In Haimentioning
confidence: 99%
“…Maintaining optimal SA requires the ability to measure SA levels frequently, and perhaps continuously, in order to determine when SA levels become suboptimal. Further, it would be ideal to be able to mitigate degraded SA, but this mitigation remains a challenge [6,9].…”
Section: Situation Awareness and Its Importance In Haimentioning
confidence: 99%
See 1 more Smart Citation